Development of a Student Grade Conversion System for Off-Campus Learning Activities: A Case Study of ITB Indonesia - kaban, Roberto; Sembiring, David JM; Br Tarigan, Ita Margaretta; Br Tarigan, Siti Jamilah (Bahasa Indonesia, 2025)
This study aims to develop a student grade conversion information system for off-campus learning programs at ITB Indonesia. The system integrates with the Academic Information System (SIAKAD) to automate and synchronize grade conversion from off-campus activities. It was developed using the Rapid Application Development (RAD) method, which prioritizes speed and user involvement. The grade conversion process is based on seven assessment components used during off-campus learning activities: activity planning (perencanaan kegiatan), implementation and outcomes (pelaksanaan dan hasil kegiatan), activity reporting (pelaporan kegiatan), personality and social aspects (aspek kepribadian dan sosial), student self-assessment (penilaian diri mahasiswa), peer assessment (penilaian sejawat), and assessment by field supervisors, local authorities, or receiving lecturers at partner institutions (penilaian dari guru pamong, supervisor, aparat desa, atau dosen penerima di perguruan tinggi tujuan). These components are processed and mapped into final scores grouped under academic and non-academic courses, taking into account their relevance to the Program Learning Outcomes (CPL) and Course Learning Outcomes (CPMK). The system provides a real-time dashboard for both students and academic supervisors to monitor the status of grade submission, conversion processes, and final results in a transparent and structured manner.